Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

What is the minimum value of the $$ \frac {x^2 + x + 1 } {x^2 - x + 1 } \ ?$$

I have solved by equating it to m and then discriminant greater than or equal to zero and got the answer, but can algebraic manipulation is possible

share|improve this question
    
You can find the minimum value of a function by setting the derivative of the function to zero and solving the resulting expression for $x$. –  Daryl Jul 25 '12 at 4:42
    
Also, you can simplify slightly by noting that $\frac {x^2 + x + 1 } {x^2 - x + 1 } = 1+\frac {2x } {x^2 - x + 1 }$. –  copper.hat Jul 25 '12 at 4:44
    
@Daryl: The question is labeled [algebra-precalculus], which would seem to mean we should check for non-calculus solutions. –  Arturo Magidin Jul 25 '12 at 4:44
add comment

3 Answers

let y=$\frac{x^2+x+1}{x^2-x+1}$

=>$x^2(y-1)-x(y+1)+(y-1)=0$

As x is real, the discriminant= $(y+1)^2-4(y-1)^2≥0$

=>$(y-3)(y-\frac{1}{3})≤0$

=>$\frac{1}{3}≤y≤3$

share|improve this answer
    
+1 Cute technique; must have missed that with my 'new maths'... –  copper.hat Jul 25 '12 at 6:23
    
To get from $1/3\leq y \leq 3$ to asserting that the minimum value is actually $1/3$, you need to demonstrate that $1/3$ is actually a possible value for $y$. In other words, you must show that there is a value of $x$ that gives this. Of course, there is, it's $x=-1$, but you really need to give this as part of your solution. –  user22805 Jul 25 '12 at 9:06
add comment

Here is an 'algebra solution':

$\frac {x^2 + x + 1 } {x^2 - x + 1 } = \frac{(x+1)^2-(x+1)+1}{(x+1)^2-3(x+1)+3} = \frac{1}{3} + \frac{2}{3} \frac{(x+1)^2}{x^2-x+1} = \frac{1}{3} + \frac{2}{3} \frac{(x+1)^2}{(x-\frac{1}{2})^2+\frac{3}{4}}$.

Since the last term is greater than zero when $x\neq -1$, we see that the minimum is

$\frac{1}{3}$.

Of course, this is cheating since I know the answer from J.D.'s solution and this suggests the way to expand the expression.

share|improve this answer
add comment

Hint: Take the derivative w.r.t $x$ and equate it with zero, you get: $$ \frac{d}{dx} \frac {x^2 + x + 1 } {x^2 - x + 1 } = - \frac {2(x^2 - 1)} {(x^2 - x + 1)^2} = 0.$$ So $x = \pm 1$ at the extrema. Test both for minimum.

Edit: this tutorial page might be helpful.

share|improve this answer
    
But again, this is not algebra as possible. –  user2468 Jul 25 '12 at 4:46
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.